2010
DOI: 10.1007/s10658-010-9678-x
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiadiazole and BABA improve resistance to Uromyces pisi (Pers.) Wint. in Pisum sativum L. with an enhancement of enzymatic activities and total phenolic content

Abstract: Benzothiadiazole (BTH) and DL-β-aminobutyric acid (BABA) induced systemic resistance was investigated in susceptible and resistant pea genotypes against Uromyces pisi. Resistance was characterized by reduced infection frequency mainly due to decreases in appressorium formation, stomatal penetration, growth of infection hyphae and haustorium formation. Changes in β-1,3-glucanase, chitinase, phenylalanine ammonia-lyase and peroxidase activities and in total phenolics content, demonstrate that U. pisi resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Peroxidase causes the oxidation of wide variety of substrates, using H 2 O 2 , such as phenol, which plays a considerable role in lignin synthesis (Goldberg et al 1987). In this study BABA caused the lowest induction effect in enhancement of peroxidase activity, and this result was in agreement with Amzalec and Chen (2007) who found that BABA have weak effect in enhancing PO activity against sunflower rust, and also with Barilli et al (2010) who found that BABA treatment weakly elicits total PO in pea genotypes against Uromyces pisi -the causal agent of pea rust. Maximum PO levels were reached three days after the application of inducers and these results are similar to results of Andres et al (2008) who found that maximum PO levels is reached four days after inoculation of wheat resistant line with the cereal cyst nematode Heterodera avenae.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Peroxidase causes the oxidation of wide variety of substrates, using H 2 O 2 , such as phenol, which plays a considerable role in lignin synthesis (Goldberg et al 1987). In this study BABA caused the lowest induction effect in enhancement of peroxidase activity, and this result was in agreement with Amzalec and Chen (2007) who found that BABA have weak effect in enhancing PO activity against sunflower rust, and also with Barilli et al (2010) who found that BABA treatment weakly elicits total PO in pea genotypes against Uromyces pisi -the causal agent of pea rust. Maximum PO levels were reached three days after the application of inducers and these results are similar to results of Andres et al (2008) who found that maximum PO levels is reached four days after inoculation of wheat resistant line with the cereal cyst nematode Heterodera avenae.…”
Section: Discussionsupporting
confidence: 90%
“…Also, our results are in accordance with Ata et al (2008) who found a significant reduction in sugar beet rust infection associated with accumulation of high level of peroxidase, PAL, free phenolic compounds and lignin content after treatment with SA and BTH. Barilli et al (2010) reported that BTH and BABA induced systemic acquired resistance in pea genotypes against rust through the enhancement of enzymatic activity and phenol accumulation. Peroxidases are enzymes involved in the cell wall strengthening through protein and other polymer oxidative cross-linking and have been associated to resistance in several plant-pathogen interactions (Wang et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenol oxidase, a copper containing enzyme, oxidizes phenolics to highly toxic quinines and is involved in the terminal oxidation of diseased plant tissue and is attributed for its role in disease resistance [33].…”
Section: Discussionmentioning
confidence: 99%
“…BTH has been shown to activate resistance in many crops against a broad spectrum of diseases such as powdery mildew in barley and wheat [11], pea rust [4] and Sclerotinia diseases in melon [5] and soybean [8]. Similar activity was found to occur in sunflower against downy mildew [3,14,24] and rust disease [20].…”
Section: Introductionmentioning
confidence: 99%